THE PECULIARITIES OF DISTRACTION REGENERATE BONE IN EXPERIMENT WHILE CHRONIC STIMULATION OF BIOLOGICALLY ACTIVE POINTS - M. E. Puseva; I. N. Mikhailov; V. Ju. Lebedinskiy; T. K. Verkhozina; T. N. Boiko (Acta Biomedica Scientifica, 2013)
In experiment the forming and remodeling of distraction regenerate in rabbits Shinshila while conducting transosseous elements through the acupuncture points were studied. One of the rabbit's forearm was stretched by Hizarov's method for 10 mm. Multidetector CT gave the results of mineral density of the bone distraction regenerate. To the 10th day of fixation of bone fragments by the external fixation device the distraction regenerate with a clear zonal structure formed. To the 20th day of fixation in the middle zone there were clear signs of the formation of the medullary canal, that proves the decrease of mineral density to negative values. The prolonged stimulation of acupuncture points by introduced transosseous elements leads to formation of the structure and properties of bone regenerate, which are close by the characteristics to the parameters of the intact bone.